1997
DOI: 10.1038/sj.onc.1201048
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish homologue of the ret receptor and its pattern of expression during embryogenesis

Abstract: The c-ret proto-oncogene, a member of the receptor tyrosine kinase gene superfamily, plays a critical role in the development of the excretory system and the enteric and autonomic nervous systems of mammalian embryos. To study the potential function of the c-ret locus in lower vertebrates, we have isolated its zebra®sh homologue, ret1 and established its expression pattern during embryogenesis. Ret1 mRNA ®rst appears during early somitogenesis in the presumptive brain, spinal cord and excretory system. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 23 publications
(33 reference statements)
3
37
1
Order By: Relevance
“…In mouse embryos, the receptor tyrosine kinase Ret is expressed early together with Phox2a in derivatives of the epibranchial placode (Pachnis et al, 1993;Valarche et al, 1993;Robertson and Mason, 1995;Tiveron et al, 1996). The zebrafish homolog of Ret, ret1, is expressed in the branchial arches (Bisgrove et al, 1997;Marcos-Gutierrez et al, 1997), and we could also detect expression in cranial neural placodes (Fig. 4E).…”
Section: Defects Of the Cranial Ganglia In Tfap2a Mutantsmentioning
confidence: 73%
“…In mouse embryos, the receptor tyrosine kinase Ret is expressed early together with Phox2a in derivatives of the epibranchial placode (Pachnis et al, 1993;Valarche et al, 1993;Robertson and Mason, 1995;Tiveron et al, 1996). The zebrafish homolog of Ret, ret1, is expressed in the branchial arches (Bisgrove et al, 1997;Marcos-Gutierrez et al, 1997), and we could also detect expression in cranial neural placodes (Fig. 4E).…”
Section: Defects Of the Cranial Ganglia In Tfap2a Mutantsmentioning
confidence: 73%
“…4D) and the imaginal retina (Fig. 4I), in keeping with the vertebrate ret expression in the eye (9,11,34).…”
Section: Expression Profile Of D-retmentioning
confidence: 94%
“…Expression of jagged and notch genes in the pronephros suggests that they could play an important role in patterning the pronephric nephron (Zecchin et al, 2005). Evidence for nephron patterning in the pronephros is seen in the segment-specific expression of ion transporters Shmukler et al, 2005), in the expression of receptors and transcription factors in discrete segments (Bisgrove et al, 1997;Marcos-Gutierrez et al, 1997;Van Campenhout et al, 2006), and in the disruption of segment-boundary formation in the pax2.1 (also known as pax2a -Zebrafish Information Network) mutant no isthmus (Majumdar et al, 2000). In our examination of cilia function in the kidney (Kramer-Zucker et al, 2005) we have found that two types of ciliated cells exist in the pronephros: single ciliated cells that have the morphology of typical transporting epithelial cells, and multiciliated cells that, by several criteria, appear specialized for fluid propulsion in the pronephros.…”
Section: Introductionmentioning
confidence: 99%